"My Friend, Ol'ga": On Rereading V. Kiselev's Novel The Girl and the Bird Plane. (2nd October 2019) - Savkina, Irina
ABSTRACT: This article examines Vladimir Kiselev's young-adult novel, The Girl and the Bird Plane [Devochka i ptitselet], written in 1966, toward the end of the Thaw. While critics in the late 1960s and the screenwriters for the novel's film version ( The Transitional Age [Perekhodnyi vozrast], 1968, directed by Richard Viktorov) interpreted the work as centering on the complex relationships existing between generations, a contemporary rereading based on categories developed within the framework of gender studies brings the novel's exploration of Soviet-era sex-role conflicts into sharp relief.